Correction: Multivalency: influence of the residence time and the retraction rate on rupture forces measured by AFM. Issue 15 (21st April 2015) - Bacharouche, Jalal; Degardin, Mélissa; Jierry, Loïc; Carteret, Cédric; Lavalle, Philippe; Hemmerlé, Joseph; Senger, Bernard; Auzély-Velty, Rachel; Boulmedais, Fouzia; Boturyn, Didier; Coche-Guérente, Liliane; Schaaf, Pierre; et al.
<x xml:space="preserve">Abstract</x> Correction for 'Multivalency: influence of the residence time and the retraction rate on rupture forces measured by AFM' by Jalal Bacharouche et al., J. Mater. Chem. B, 2015, 3, 1801–1812.